Experimental study of a composite beam externally bonded with a carbon fiber-reinforced plastic plate - Zhang, Wei; Kang, Shuaiwen; Liu, Xiang; Lin, Benqing; Huang, Yiqun (Journal of Building Engineering, 2023)
According to the characteristics of steel fiber reinforced concrete (SFRC) with high tensile strength and carbon fiber reinforced plastic (CFRP) with high strength and light weight, a composite beam composed of CFRP plate, SFRC and ordinary concrete (OC) is developed in the paper. Eight specimens, including four CSOCBs with different heights of the SFRC and four SFRC–OC composited beams with varying heights of the SFRC, were tested to analyze the flexural behavior. The results show that the composite beam composed of OC, SFRC and CFRP improves the ultimate load capacity of the beam under unidirectional load, enhances the cracking and deformation resistance of the beam, and solves the defects of the weak tensile capacity of ordinary concrete beams. Applying them to the building structure can improve the stability of the structure and prolong the service life of the building. A prediction model for the bending capacity of the CSOCB was proposed and validated. Based on the limit state design method, the design formula for the bending capacity of the composite beam is described in detail herein. •A composite beam composed of carbon fiber reinforced plastic (CFRP), steel fiber reinforced concrete (SFRC) and ordinary concrete (OC) was developed.•A prediction model for the bending capacity of the CSOCB was proposed and validated.•The design formula for the bending capacity of the composite beam is described based on reliability analysis.